The Global Impact of Demographic Change - Callen, Tim (IMF Working Papers; Working Paper, 2006)
The world is in the midst of a major demographic transition. This paper examines the implications of such transition over the next 80 years for Japan, the United States, other industrial countries, and the developing regions of the world using a dynamic intertemporal general equilibrium four-country model containing demographics calibrated to the "medium variant" of the United Nations population projections. We find that population aging in industrial countries will reduce aggregate growth in these regions over time, but should boost growth in developing countries over the next 20-30 years, as the relative size of their workingage populations increases. Demographic change will also affect saving, investment, and capital flows, implying changes in global trade balances and asset prices. We also explore the sensitivity of the results to assumptions about future productivity growth and country external risk for the developing country region.